Kepuasan Pelanggan Generasi Z di KFC Lippo Village pada Masa Pandemi COVID-19 - Kevin Gustian Yulius; Agatha Putri Wikumala; Priscillia Priscillia (PolimdoSains, 2023)
Customer satisfaction is an important factor in the sustainability of a business, especially in the service industry. This study analyzes the factors that influence customer satisfaction at a fast food restaurant, KFC, in Lippo Village, Tangerang. The unit of analysis in this study is the Z generation, which has different satisfaction determinants from the previous generation. The four independent variables used are food quality, service quality, physical environment quality, and the COVID-19 health protocol. This research is an explanatory research that explain the relationship between the four independent variables and one dependent variable partially and simultaneously. The sampling technique is non-probability sampling with purposive sampling and the time dimension in this study is cross-sectional, where samples are taken at a certain time period, namely in 2022. The research instrument used is a questionnaire which is distributed online and the data results are processed using IBM SPSS 25 software. The results indicate that the four independent variables have a significant influence on customer satisfaction partially and simultaneously, but with a coefficient of determination below 50%. Subsequent research is suggested to add the independent variables used in the model or consider using customer satisfaction as an intervening variable.